"قواعد النيات والمقاصد عند الحافظ العراقي وابنه الحافظ أبي زرعة من خلال كتابهما "طرح التثريب: Fiqh Principles Regarding Intention in the Book of "Tharh al-Tatsrib" by al-Hafizh al-Iraqi and His Son, al-Hafizh Abu Zur'ah - Muhammad Ikhsan; Hassani Mohammed Nour (البصيرة: مجلة الدراسات الإسلامية, 2021)
This study aims to explore the principles of the Islamic law that govern the intentions and intentions of the mukallaf in the views of al-Hafizh al-Iraqi and his son, al-Hafizh Abu Zur'ah, in their work, Tharh al-Tatsrib. This research seeks to raise the position of al-Hafizh al-Iraqi and his son, al-Hafizh Abu Zur'ah, in the study of Islamic law, through a study of fiqh principles relating to the intention of mukallaf and their application in Islamic law. The method used in this research is the inductive method and legal analysis. Among the important conclusions of this research is that there are at least 10 rules related to intention in the Book of Tharh al-Tatsrib, all of which are then explained the arguments and applications of Islamic law. This research also found the superiority of al-Hafizh al-Iraqy and his son, al-Hafizh Abu Zur'ah, in the study of Islamic law, although both were more popular in the study of hadith; which is shown by their interaction with the rules of Islamic law in their work, Tharh al-Tatsrib.